Agrobacterium rhizogenes-mediated transformation of a dioecious plant model Silene latifolia - Hudzieczek, Vojtech; Cegan, Radim; Cermak, Tomas; Bacovska, Nela; Machalkova, Zuzana; Dolezal, Karel; Plihalova, Lucie; Voytas, Daniel; Hobza, Roman; Vyskot, Boris (New biotechnology, 2019)
Silene latifolia serves as a model species to study dioecy, the evolution of sex chromosomes, dosage compensation and sex-determination systems in plants. Currently, no protocol for genetic transformation is available for this species, mainly because S. latifolia is considered recalcitrant to in vitro regeneration and infection with Agrobacterium tumefaciens. Using cytokinins and their synthetic derivatives, we markedly improved the efficiency of regeneration. Several agrobacterial strains were tested for their ability to deliver DNA into S. latifolia tissues leading to transient and stable expression of the GUS reporter. The use of Agrobacterium rhizogenes strains resulted in the highest transformation efficiency (up to 4.7% of stable transformants) in hairy root cultures. Phenotypic and genotypic analyses of the T1 generation suggested that the majority of transformation events contain a small number of independent T-DNA insertions and the transgenes are transmitted to the progeny in a Mendelian pattern of inheritance. In short, we report an efficient and reproducible protocol for leaf disc transformation and subsequent plant regeneration in S. latifolia, based on the unique combination of infection with A. rhizogenes and plant regeneration from hairy root cultures using synthetic cytokinins. A protocol for the transient transformation of S.latifolia protoplasts was also developed and applied to demonstrate the possibility of targeted mutagenesis of the sex linked gene SlAP3 by TALENs and CRISPR/Cas9.
Keywords: exprese genu; Gene Expression; TALENs; Regeneration; In vitro regeneration; Silene; Silene latifolia; Genetic transformation; reportérové geny; Protoplast assay; transformace genetická; molekulární evoluce; Evolution, Molecular; Genetic Techniques; Models, Genetic; chromozomy rostlin; regenerace; Chromosomes, Plant; Transformation, Genetic; DNA, Bacterial; CRISPR-Cas Systems; DNA bakterií; Plants, Genetically Modified; genetické techniky; Agrobacterium; modely genetické; CRISPR-Cas systémy; Transcription Activator-Like Effector Nucleases; geneticky modifikované rostliny; Genes, Reporter; CRISPR/Cas9